Maximum power tracking for photovoltaic energy conversion system - Maung Zaw Naing. (2008)
Photovoltaic systems convert light energy into electricity. Photovoltaic cells or solar cells rely on the photovoltaic effect to absorb the energy of the sun and cause current to flow between two oppositely charge layers. A solar cell has a maximum power operating point (MPOP) which varies with changing atmospheric conditions, radiation and temperature. The current produced by a solar cell depends on the voltage, i.e. the current is the function of the voltage and therefore the generated power can be varied.